Hypertension Expert System with C5.0 Algorithm and Fuzzy Logic - I Gusti Made Ngurah Ardi Yasa; I Ketut Gede Darma Putra; Ni Md Ika Marini Mandenni (Institute of Advanced Engineering and Science, 2014)
Expert System is a knowledge -based system which is its knowledge is coming from the experts itself. This system is expected to help users to take best decisions in solving the problems they face. This expert system can be applied in various field of knowledges. Medical field is one area where expert system is needed in case of taking decision, such as diagnosing and treatment.Hypertension is one of medical disease that can be diagnosed from looking at the patient’s physical characteristics and the patient’s lifestyle. Beside using the experts knowledge in diagnosing process, we also combine it with C5.0 algorithms and fuzzy logic to get precise result. C5.0 algorithm is used to create a decision tree based on the experts, while fuzzy logic used to categorize the type of hypertensive disease that suffered by the patient and increase the level of accuracy of the diagnosing system. The accuracy of the combination between c5.0 algorithm and fuzzy logic is about 97.19%.